PERSEPSI MASYARAKAT TERHADAP KESENIAN GANDANG TAMBUA DI DESA TALAGO SARIAK KECAMATAN PARIAMAN TIMUR - Lidia Nusir; Syeilendra Syeilendra; Yensharti Yensharti (FBS Universitas Negeri Padang, 2013)
Abstract This research was aimed at describing the perception of the people toward Gandang Tambua show in Desa Talago Sariak Kecamatan Pariaman Timur. This was a qualitative research which used descriptive method. The data was collected through library study, observation, questionnaires and interview. The result of the research indicated that the people had positive perception toward the Gandang Tambua show and expected that this should be perpetuated and developed in the future. The figures of the society, the youth and the local government were suggested to work cooperatively to promote this art show as one of the typical characteristics of Pariaman especially Desa Talago Sariak. Kata Kunci: Persepsi, Gandang Tambua.